Shadowing the White Man's Burden : U.S. Imperialism and the Problem of the Color Line. - Murphy, Gretchen, 1971- (America and the long 19th century., 2010)
During the height of 19th century imperialism, Rudyard Kipling published his famous poem "The White Man's Burden." While some of his American readers argued that the poem served as justification for imperialist practices, others saw Kipling's satirical talents at work and read it as condemnation. Gretchen Murphy explores this tension embedded in the notion of the white man's burden to create a new historical frame for understanding race and literature in America. Shadowing the White Man's Burden maintains that literature symptomized and channeled anxiety about the racial components of the U.S.